Malaria in the UK: past, present, and future. Issue 949 (10th November 2004) - Chin, T; Welsby, P D
Abstract : There is strong evidence that malaria was once indigenous to the UK, that global warming is occurring, and that human activity is contributing to global warming. Global warming will have a variety of effects, one of which will probably be the return of indigenous malaria.